Entamoeba infections and associated risk factors among migrant workers in peninsular Malaysia - Sahimin, Norhidayu; Yunus, Muhammad Hafiznur; Douadi, Benacer; Lim, Yvonne Ai Lian; Noordin, Rahmah; Behnke, Jerzy Marian; Mohd Zain, Siti Nursheena (Malaysian Society of Parasitology and Tropical Medicine, 2019)
The influx of low skilled migrant workers to Malaysia from low socio-economic countries where gastrointestinal parasitic infections are prevalent has raised concerns about transmission to the local population. Three methods for detection (serology, microscopy and molecular techniques) were utilized to identify Entamoeba infections amongst the targeted cohort and determine risk factors associated with infection. Serological screening of 484 migrant workers from five working sectors in Peninsular Malaysia using IgG4 ELISA based on the rPPDK antigen showed an overall seroprevalence of 7.4% (n = 36; CL95 = 5.3–10.1%) with only one factor statistically associated with seropositivity of anti-amoebic antibodies, i.e. years of residence in Malaysia (χ21 = 4.007, p = 0.045). Microscopic examination of 388 faecal samples for protozoan cysts and trophozoites showed a slightly higher prevalence (11.6%; n=45; CL95: 8.4–14.8%). Meanwhile, amplification of the 16S rDNA gene detected two species i.e. Entamoeba dispar (23/388; 5.9%; CL95: 3.6–8.3%) and E. histolytica (11/388; 2.8%; CL95: 1.2–4.5%) and mixed infections with both parasites in only three samples (3/388; 0.8%; CL95: 0.2–2.2%). Entamoeba dispar infection was significantly associated with those employed in food and domestic services (χ24 = 12.879, p = 0.012). However, none of the factors affected the prevalence of E. histolytica infection. Despite the low prevalence of E. histolytica in faecal samples of the study cohort, the presence of this pathogenic parasite still poses potential public health risks and calls for tighter control strategies based on better availability of chemotherapeutic treatment and accessibility to appropriate health education. © 2019, Malaysian Society for Parasitology. All rights reserved.